Determinação do acetato de megestrol em plasma humano por cromatrografia líquida de alta eficiência acoplada ao espectrômetro de massa : aplicação em estudo de bioequivalência - Martins, Ismael Leite (2004)
A sensitive and highly selective liquid chromatography-tandem mass spectrometry (LC-MS-MS) method was developed to determine megestrol acetate in human plasma using betamethazone as the internal standard. The analyte and internal standard were extracted from plasma samples by hexane/ethyl acetate (1:1 v/v), and chromatographed on a C18 column. The mobile phase consisted of acetonitrila-water (80:20 v/v) including formic acid 0.1%. Detection was performed on a triple quadropole tandem mass spectrometer by multiple reaction mode via electrospray source. The method has a chromatographic run time of 3 min and a limit of quantification of 2 ng/mL. The linear calibration curves were obtained in the concentration range 2 – 150 ng/mL. The intra-batch precisions were 3.16%, 4.65%, and 2.68%; and the intra-batch accuracy was 6.77%, 6.23%, and 5.73% for 6, 60 and 120 ng/mL, respectively. The inter-batch precision was 7.76%, 6.23%, and 6.37% and the inter-batch accuracy was 0.08%, 1.55%, and 2.11% for the same concentrations. This validated method was successfully applied for the determination of pharmacokinetic profiles of megestrol acetate tablets administered to 30 healthy volunteers.